Lumber quality of Eucalyptus grandis as a function of diametrical position and log steaming - Durgante Severo, Elias Taylor [UNESP]; Calonego, Fred Willians [UNESP]; Oliveira de Matos, Carlos Alberto [UNESP] (Elsevier B.V., 2010)
The objective of this study was to evaluate the effect of log steaming and of the diametrical position of boards on the timber quality of Eucalyptus grandis. Logs with diameters between 20 and 25 cm, between 25 and 30 cm and between 30 and 35 cm were studied. Half of logs were kept in its original condition, and the other half was steamed at 90 degrees C for 20 h. Later, the logs were cut into flat saw boards, and defects due to growth stress relief were measured. The results show that: (1) boards from control logs show different magnitudes of cracking according to the diameter of the log and the diametrical position of the board: (2) boards from logs with diameters between 30 and 35 cm and those from next to the pith develop larger cracks; and (3) boards from steamed logs show a reduction in the magnitude of cracking and a homogenous distribution of this defect relative to diametrical position within the log. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Eucalyptus grandis; Cracking; Log steaming; Flat saw boards; Diametrical position